2020
DOI: 10.1055/s-0040-1713607
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Musculoskeletal Pain Generators Using Clinical PET

Abstract: Identifying the source of a person's pain is a significant clinical challenge because the physical sensation of pain is believed to be subjective and difficult to quantify. The experience of pain is not only modulated by the individual's threshold to painful stimuli but also a product of the person's affective contributions, such as fear, anxiety, and previous experiences. Perhaps then to quantify pain is to examine the degree of nociception and pro-nociceptive inflammation, that is, the extent of cellular, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Studies in human medicine have demonstrated that the functional information obtained with 18 F-Sodium Fluoride (NaF) PET is a pertinent addition to the structural information provided by CT or MRI, leading to the identification of lesions not readily apparent using other imaging techniques and providing valuable information in determining the activity of lesions. [3][4][5][6][7][8][9][10] A previous pilot study demonstrated that 18 F-NaF PET identified stress remodeling lesions in the fetlocks of Thoroughbred racehorses. 11 18 F-NaF uptake was identified most commonly in the palmar metacarpal condyles and in the proximal sesamoid bones, at sites where catastrophic breakdowns occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in human medicine have demonstrated that the functional information obtained with 18 F-Sodium Fluoride (NaF) PET is a pertinent addition to the structural information provided by CT or MRI, leading to the identification of lesions not readily apparent using other imaging techniques and providing valuable information in determining the activity of lesions. [3][4][5][6][7][8][9][10] A previous pilot study demonstrated that 18 F-NaF PET identified stress remodeling lesions in the fetlocks of Thoroughbred racehorses. 11 18 F-NaF uptake was identified most commonly in the palmar metacarpal condyles and in the proximal sesamoid bones, at sites where catastrophic breakdowns occur.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with planar scintigraphy commonly used in equine bone scans, PET has the advantage of providing cross‐sectional imaging, resulting in more specific localization of lesions. Studies in human medicine have demonstrated that the functional information obtained with 18 F‐Sodium Fluoride (NaF) PET is a pertinent addition to the structural information provided by CT or MRI, leading to the identification of lesions not readily apparent using other imaging techniques and providing valuable information in determining the activity of lesions 3–10 …”
Section: Introductionmentioning
confidence: 99%
“…More research is needed on the specific mechanisms that initiate and perpetuate the MTrP in MPS, 8 which in the future could lead to the development of targeted therapies. Furthermore, should any of these markers prove to have high specificity for the disease, it could be possible to create targeted radioligands and use molecular imaging techniques, such as positron emission tomography 59,60 . Recently, systems capable of systemic positron emission tomography imaging at significantly lower dose have become available 61,62 and could provide a unique molecular-level in vivo picture of MTrPs and MPS pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…(Reproduced with permission from Yoon D, Kogan F, Gold GE, Biswal S. Identifying musculoskeletal pain generators using clinical PET. Semin Musculoskelet Radiol 2020;24(4):441-450) 43 and function of S1Rs. 43 Therefore, radiotracers designed to detect the S1R can aid in locating nerve inflammation.…”
Section: Imaging Of Sigma-1 Receptorsmentioning
confidence: 99%
“…Semin Musculoskelet Radiol 2020;24(4):441-450) 43 and function of S1Rs. 43 Therefore, radiotracers designed to detect the S1R can aid in locating nerve inflammation.…”
Section: Imaging Of Sigma-1 Receptorsmentioning
confidence: 99%